An efficient parallel method for photo-realistic fluid animation. Issue 2 (23rd February 2017) - Zhang, Guijuan; Zhao, Jinyan; Xu, Weizhi; Lu, Dianjie; Wang, Yongjian; Meng, Xiangxu
ABSTRACT: Fluid animation often appears in applications such as games, films and cartoons. How to animate photo-realistic fluid motion efficiently is an important issue. We present an efficient parallel method for photo-realistic fluid animation in this paper. Our method is designed to generate fluid animation results with high efficiency on a cluster system. To do this, we categorize the computers in our cluster system into two classes, the server and the client. The server controls the process of the fluid animation while the clients are responsible for numerical computation. Given 3D virtual environment and fluid initial condition, we make pre-processing on the server so as to decompose the fluid animation task into several subtasks. Thus, the computation domain is divided into blocks and each client executes numerical computation for one block. The blocks of two adjacent clients are overlapped to keep the continuity of the solution across subdomain interface. We demonstrate the efficiency of our method by animating the motion of smoke and liquid. Results show that the proposed parallel algorithm can improve the computation speed of physically-based fluid animation significantly while getting interesting fluid details. GRAPHICAL ABSTRACT: